Non-pharmacological methods for labor pain relief: What does the literature say? (Research, Society and Development, 2025)
Introduction: Labor pain is considered one of the most intense experiences in a woman’s reproductive life and is influenced by physiological, emotional, and cultural factors. In recent decades, the increasing medicalization of childbirth has expanded the use of pharmacological analgesia, although non-pharmacological methods have been recommended as safe, accessible, and woman-centered strategies. Objective: To synthesize scientific evidence on the effectiveness of non-pharmacological methods for pain relief during labor. Method: Observational and descriptive literature review based on clinical studies, systematic reviews, meta-analyses, and technical guidelines identified in PubMed, SciELO, and CAPES databases, using descriptors related to non-pharmacological pain management in labor. Results: Evidence shows that interventions such as hydrotherapy, massage, upright positions, breathing techniques, music therapy, acupressure, and continuous support significantly reduce pain scores, promote physiological progression of labor, and increase maternal satisfaction. Multimodal protocols demonstrated greater effectiveness compared to isolated methods, with reduced need for pharmacological analgesia and fewer obstetric interventions. Conclusion: Non-pharmacological methods are effective and humanized approaches for labor pain relief. Their systematic adoption can improve maternal experience and promote safer childbirth, underscoring the need for broader implementation in health services and professional training for their appropriate use.